Pengaruh Return On Asset (ROA), Return On Equity (ROE), Dan Earning Per Share (EPS) Terhadap Harga Saham Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - I Wayan Eka Saputra (UNHI Press, 2023)
The capital market is a very effective mechanism for sourcing and distributing funds to businesses. When looking for a good company to invest in, many investors first look to the manufacturing sector. The possibility of financial gain serves as an incentive for takingmeasured risks and is thus a major lure to the world of investing. Partial test results showing a significance score of 0.199>0.05 suggest that Return On Assets (ROA) has no discernible effect on stock prices for manufacturing companies. Stock prices of manufacturing companies are not significantly affected by return on equity (ROE), since the significance value is bigger than.05 (0.381). A positive and statistically significant correlation between earnings per share and stock prices is shown by a significance value of 0.00000005. The EPS measures how much of a company's profit is returned to shareholders. The higher and more stable a stock's EPS, the greater its market value